Recent Advances in the Role of Natural Killer Cells in Acute Kidney Injury - Cantoni, Claudia; Granata, Simona; Bruschi, Maurizio; Spaggiari, Grazia Maria; Candiano, Giovanni; Zaza, Gianluigi (Frontiers in Immunology, 2020)
Growing evidences are revealing a central role for Natural Killer (NK) cells, cytotoxic cells belonging to the emerging family of Innate Lymphoid Cells (ILCs), in acute and chronic forms of renal disease. NK cell effector functions include both the recognition and elimination of virus infected and tumor cells and the capability of sensing pathogens through Toll-like receptor (TLR) engagement. Notably, they also display immune regulatory properties, exerted thanks to their ability to secrete cytokines/chemokines and to establish interactions with different innate and adaptive immune cells. Therefore, because of their multiple functions, NK cells may have a major pathogenic role in acute kidney injury (AKI), and a better understanding of the molecular mechanisms driving NK cell activation in AKI and their downstream interactions with intrinsic renal cells and infiltrating immune cells could help to identify new potential biomarkers and to select clinically valuable novel therapeutic targets. In this review, we discuss the current literature regarding the potential involvement of NK cells in AKI.